Las energías renovables ¿es posible hablar de un Derecho Energético Ambiental? Elementos para una discusión (2015)
This paper poses, as central thesis, the insurmountable need to introduce competitive renewable energy within the energy basket for the necessary consolidation of the causal relationship among energy, environment, and economic development. The abovementioned derives from the following query: What is the role of renewable energies within the energy system and its importance to the energy crisis? The thesis implies that energy, environment and economic development are core elements for the construction of an Environmental Energy Law. Hence, in order to consolidate a proper connection among these elements, clean energy shall be incorporated within the energy basket, with the purpose of competing against fossil fuels, based on the State’s regulative faculty as a public prerogative.